Design and optimization of mechanical engineering products - Kumar, K. (Kaushik), 1968-; Davim, J. Paulo (IGI Global, 2018)
"This book provides the design of new products, redesign of existing products with different materials improving properties, optimized product design, alternative design methodology for betterment, redesign of mechanical equipment and products with alternative parts enhancing performance"--